Mens Rea Representation In Pandji Pragiwaksono's Public Communication: A Communicative Action and Mass Communication Theory Perspective - Adinda Rahmi Aisyah; Yusalina (Indonesian Scientific Publication, 2026)
This study examines communicative intent (mens rea) in Pandji Pragiwaksono's public communication through his Netflix stand-up special MensRea(2025), which triggered widespread controversy in Indonesia's digital public sphere. Despite growing scholarship on political satire and digital communication, little attention has been given to the gap between communicator intent and audience interpretation in the Indonesian context. This research employed qualitative online media observation conducted from March to May 2026, using systematic keyword searches across designated digital platforms. Data were drawn from the Netflix special as primary corpus, supplemented by YouTube podcast content, social media posts, and national online news coverage. Sentiment data were sourced from Drone Emprit and DataIndonesia.id. Pandji's communicative mens rea was consistently identified as an intent to deliver socio-political critique through satire across four dimensions lexical, contextual, consistency, and responsive with significant sentiment polarization between online media (53.2% negative) and social media (66.1% positive). Mens Rea demonstrates comedy's capacity as a political mirror, while media framing and the absence of a shared normative framework rather than communicator failure alone contributed significantly to public polarization. Findings suggest implications for communication ethics, media coverage standards, and regulatory frameworks in Indonesia's digital public sphere.